The Customer Interest in Using Bank Syariah Indonesia Mobile BSI in Jambi Province - Romi Hidayat; Darmawan; Muhammad ahsanul amal; Sabardin; Shabur, Usman (Indonesian Journal of Economics and Management, 2025)
Bank Syariah Indonesia customers in Jambi Province have great potential in using BSI Mobile. However, the use of BSI Mobile is not yet optimal. It is indicated that BSI customers in Jambi Province are hampered by the lack of branch offices in every district/city in Jambi Province. This has hampered customers' interest in using BSI Mobile. This study aims to evaluate the impact of perceived ease of use, perceived benefits, perceived risk, service quality, and sharia compliance on the interest in using BSI Mobile Bank Syariah Indonesia in Jambi Province. Using quantitative methodology, this research involved 272 respondents/customers and utilized the SmartPLS analysis technique. In this study, interest in using BSI Mobile is negatively and significantly influenced by risk perception, but positively and significantly influenced by perceived usefulness, sharia compliance, service quality, and ease of use. The findings of this study imply that customers are more interested in utilizing BSI Mobile when companies provide higher quality services. This research recommends that Bank Syariah Indonesia (BSI) in Jambi Province improve the features on BSI Mobile and provide discounts or cashback on payments/transactions through the use of BSI Mobile. Keywords: Interest, Perceived Ease Of Use, Perceived Usefulness, Perceived Risk, Service Quality And Sharia Compliance